1992
DOI: 10.1001/archderm.1992.01680180125022
|View full text |Cite
|
Sign up to set email alerts
|

The Rule of Hand: 4 Hand Areas=2 FTU=1 g

Abstract: In January 1990, multiple glossy, slightly erythematous, infiltrated plaques developed; these plaques had violaceous borders on the ab¬ domen, the back, and both legs ( Figure). The patient was still being treated with prednisone (10 mg/d) and chloroquine (100 mg/d). His¬ tologie examination of a skin lesion showed a thickened dermis with a homogeneous stratum papillare; some dilated capillaries; and coarse, bundled collagen. These findings confirmed our clinical diag¬ nosis of morphea.Thus, 1 year after EF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 4 publications
3
44
0
1
Order By: Relevance
“…We were therefore interested in RJ Perry and colleagues' findings,1 which closely agree with ours 2. We compared the area of one side of a hand (with the fingers and thumb pulled together) with the calculated body surface area in 50 adults and found that the hand represented a mean of 0.76% of the body surface area in men and 0.70% in women.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…We were therefore interested in RJ Perry and colleagues' findings,1 which closely agree with ours 2. We compared the area of one side of a hand (with the fingers and thumb pulled together) with the calculated body surface area in 50 adults and found that the hand represented a mean of 0.76% of the body surface area in men and 0.70% in women.…”
supporting
confidence: 75%
“…We compared the area of one side of a hand (with the fingers and thumb pulled together) with the calculated body surface area in 50 adults and found that the hand represented a mean of 0.76% of the body surface area in men and 0.70% in women. This information was used to devise the “rule of hand,” a simple method for determining the amount of topical treatment to prescribe 2. The rule states that four (adult) hands is equivalent to 1 g or two fingertip units 3.…”
mentioning
confidence: 99%
“…However, when using medium rank topical corticosteroids, twice‐a‐day application is more effective than once‐a‐day application (evidence level II) 33 Application amount of topical corticosteroids: A finger‐tip unit (FTU) is the amount of ointment expressed from a tube with a 5‐mm diameter nozzle and measured from the distal skin‐crease to the tip of the index finger (∼0.5 g); this is an adequate amount for application to two adult hand areas, which is approximately 2% of an adult body surface area 34,35 …”
Section: Treatmentmentioning
confidence: 99%
“…Lastly, we consider that it is appropriate to consider 1 FTU = 0.25 g (4 FTU = 1 g) but not 1 FTU = 0.5 g (2 FTU = 1 g) when prescribing steroid ointments in 5-gram tubes (2). Moreover, the 'rule of hand', that states 1 FTU of ointment covers the area of two handprints (3), should be reconsidered when prescribing ointments packed in such small tubes with small nozzles.…”
Section: Ftu (G) = Amentioning
confidence: 99%